Lesbians in Revolt - Bunch, Charlotte (Lesbianism and the women's movement, 1975)
Keywords: 1900-1999; amériques; approches et analyses; cours; discipline; fem1000; lesbianisme; militance; mouvements des femmes*; pol4212; premier cycle; périodes historiques; régions géographiques; science politique; science politique et droit; thématiques; états-unis

Lesbianism and the women's movement - Myron, Nancy; Bunch, Charlotte (Diana Press, 1975)
This book outlines the essence of lesbian/feminist politics and documents how the women's movement has responded to it. In so doing it critiques heterosexuality and shows why lesbianism is one of the fundamental issues of feminism today. The articles collected here were written by the Furies and/or taken from Furies publications over a two-year period.
Keywords: 1900-1999; approches et analyses; cours; fem1000; lesbianisme; militance; mouvements des femmes*; premier cycle; périodes historiques; thématiques

Le corps lesbien - Wittig, Monique (Éditions de minuit, 1973)
Le lesbianisme est traité selon une dimension poétique : le corps féminin est énuméré selon ses différentes parties, et se présente comme un manifeste de la révolte féminine, écrit par une femme, pour les femmes.
Keywords: 1900-1999; 1970-1979; approches et analyses; arts; corps; corps féminin; cours; discipline; europe; fem1000; france; lesbianisme; premier cycle; périodes historiques; régions géographiques; thématiques; études littéraires